BEYOND THE GUT: EXPLORING NEUROLOGICAL IMPLICATIONS OF CELIAC DISEASE - Karol Sikora; Monika Rogowska; Karolina Wojdat-Krupa; Weronika Ossowska; Maksymilian Czarnota; Klaudia Płudowska; Aleksandra Przelaskowska; Paulina Lewaśkiewicz; Jan Puliński (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: The aim of this article is to provide a comprehensive review of the neurological manifestations associated with celiac disease (CD), a systemic autoimmune disorder triggered by gluten in genetically predisposed individuals. Although CD is traditionally associated with gastrointestinal symptoms, its neurological effects are increasingly recognized and require further analysis. Material and methods: This narrative review was conducted using literature sourced from scientific databases including PubMed, Scopus, Web of Science, and Google Scholar. State of knowledge: Neurological symptoms in CD, such as cerebellar ataxia, peripheral neuropathy, cognitive impairment, seizures, and”brain fog, ” may precede or occur without gastrointestinal symptoms. Diagnostic strategies include genetic and serological testing, neuroimaging, and neurological assessments. Although a gluten-free diet remains the cornerstone of therapy, additional treatments such as vitamin E supplementation and intravenous immunoglobulin have shown promise in specific cases. Results: Neurological symptoms affect a significant proportion of patients with celiac disease, and early diagnosis combined with strict adherence to a gluten-free diet improves treatment outcomes. Quality of life and mental well-being also improve, which is particularly noticeable in the first year of treatment. Celiac disease is characterized by a diverse spectrum of neurological symptoms that may remain undiagnosed without a multidisciplinary approach.